Inorganic Semiconductor Quantum Dots as a Saturated Excitation (SAX) Probe for Sub‐Diffraction Imaging. Issue 3 (16th November 2020) - Kumar Singh, Avinash; Burkhow, Sadie J.; Wijesooriya, Chamari; Boote, Brett W.; Petrich, Jacob W.; Smith, Emily A.
Abstract: The photoluminescence (PL) saturation of CdSe/ZnS core/shell inorganic semiconductor quantum dots (QDs) and its utility as a probe for saturated excitation (SAX) microscopy are reported. Under saturating excitation power densities, the PL signal was demodulated and recorded at harmonics of the fundamental frequency. For commercially available Qdot® 655 ITK™ QDs, the power density required to achieve saturation was dependent upon the local environment of the QDs. For QDs deposited and dried on a glass substrate, the excitation power density required for PL saturation was less than 1 kW/cm 2 . Compared to this, saturation of PL for QDs dispersed in water required an excitation power density greater than 200 kW/cm 2 . This observation is manifested as a limitation in the imaging of hydrated samples, as demonstrated for HeLa cells labelled with biotinylated‐phalloidin followed by labelling with streptavidin‐coated QDs. As saturation affects the obtained spatial resolution in several imaging formats, including confocal imaging, the provided data will aid in obtaining the optimal spatial resolution when using QD probes to image biological samples. Abstract : Bright light : Saturation of the population difference requires a higher intensity of excitation light when commercial CdSe/ZnS core/shell quantum dots are dispersed in water compared to when they are dried on a glass coverslip as a dense film.